Exploring Genetic Variants in Epidermal Differentiation Complex Genes in Severe Atopic Dermatitis: A Case Series - Batbileg, Lkhamdari; Baasanjav, Sevjidmaa; Tulgaa, Khosbayar; Nyamdavaa, Khurelbaatar; Yadamsuren, Enkhtur; Biziya, Baasanjargal (Central Asian Journal of Medical Sciences, 2024)
Objective: The complex interplay between genetic and external factors contributes to the multifactorial nature of atopic dermatitis (AD). The study aimed to use next-generation sequencing (NGS) to identify and describe genetic alterations and polymorphisms in the epidermal differentiation complex (EDC) in two children with severe atopic dermatitis. Methods: A case-series study was conducted involving two children with severe atopic dermatitis, selected from a group of 103 based on questionnaire data, clinical manifestations (SCORAD index, skin moisture, trans-epidermal water loss), and laboratory tests (total IgE levels). Whole-exome sequencing (WES) was performed to analyze their genomic DNA. Results: Among the two participants, gene variants related to skin conditions, allergies, autoimmune disorders, and neurometabolic disorders were identified. Both participants exhibited variants in FLG, HRNR, and SPRR1B genes located in the Epidermal differentiation complex. Among these genetic variants, classifications such as “VUS/Weak Pathogenic” and “Likely Pathogenic” were observed, and synonymous variants were found alongside missense. A significant finding was the identification of rare alleles not documented in allele frequency databases. Conclusion: Identifying various alleles highlighted those multiple gene variants, acting together, may contribute to the development of the disease, warranting further investigation.